Associations between education and brain structure at age 73 years, adjusted for age 11 IQ. (25th October 2016) - Cox, Simon R.; Dickie, David Alexander; Ritchie, Stuart J.; Karama, Sherif; Pattie, Alison; Royle, Natalie A.; Corley, Janie; Aribisala, Benjamin S.; Valdés Hernández, Maria; Muñoz Maniega, Susana; Starr, John M.; Bastin, Mark E.; et al.
Abstract : Objective: To investigate how associations between education and brain structure in older age were affected by adjusting for IQ measured at age 11. Methods: We analyzed years of full-time education and measures from an MRI brain scan at age 73 in 617 community-dwelling adults born in 1936. In addition to average and vertex-wise cortical thickness, we measured total brain atrophy and white matter tract fractional anisotropy. Associations between brain structure and education were tested, covarying for sex and vascular health; a second model also covaried for age 11 IQ. Results: The significant relationship between education and average cortical thickness (β = 0.124, p = 0.004) was reduced by 23% when age 11 IQ was included (β = 0.096, p = 0.041). Initial associations between longer education and greater vertex-wise cortical thickness were significant in bilateral temporal, medial-frontal, parietal, sensory, and motor cortices. Accounting for childhood intelligence reduced the number of significant vertices by >90%; only bilateral anterior temporal associations remained. Neither education nor age 11 IQ was significantly associated with total brain atrophy or tract-averaged fractional anisotropy. Conclusions: The association between years of education and brain structure ≈60 years later was restricted to cortical thickness in this sample; however, the previously reported associations between longer education and a thicker cortex are likely to be overestimates in terms of both magnitude and distribution. This finding has implications for understanding, and possibly ameliorating, life-course brain health.